Community Empowerment Towards Proklim Based on the Implementation of a Green Economy in Petukangan Utara Village - Martini; Tri Endangsih; Yousep Eka Irawan A.; Chairunisa Nabila Putri; Azeeza Salsabila Nasution (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This community engagement initiative aims to accelerate the realization of a ProKlim (Program Kampung Iklim) model village in Petukangan Utara, South Jakarta, through participatory environmental empowerment. The intervention integrates four environmentally adaptive technologies: biopore infiltration holes, vertical garden systems, composting machines for organic waste management, and community-based aquaponics. The program enhances residents’ environmental awareness and equips them with practical skills in waste reduction, water and soil conservation, and urban food production. The results show significant improvements in community participation, reduction of household organic waste, the establishment of productive green spaces, and the development of a sustainable environmental stewardship culture.